Optimizing Staffing Models and Team Structure : For Quality Care Amidst Infrastructure and Resource Constraints - World Bank Group (World Bank, Washington, DC, 2019)
In low, and middle-income countries, policymakers have long struggled to extend quality frontline care to remote, rural communities. Confronting poor infrastructure, health worker shortages, and limited fiscal space, many countries have used expanded community-based health worker cadres to improve ‘last mile’ access to essential services. Yet to date, many such initiatives have been hampered by poor service quality, insufficient support, and lack of wider integration, ultimately yielding disappointing results. To harness the potential of frontline health staff in these settings, innovative staffing models are needed to integrate community health workers (CHWs) and mid-level cadres within effective frontline health teams.